Case Report: A rare presentation of short posterior ciliary artery occlusion with paracentral acute middle maculopathy - Yuanmin, Dai; Jiehui, Xu (Frontiers in Medicine, 2025)
The occlusion of the short posterior ciliary arteries (SPCAs), a severe yet infrequent ocular vascular pathology, becomes particularly uncommon when it coexists with paracentral acute middle maculopathy (PAMM). We report a rare instance involving a middle-aged male who experienced an occlusion of the posterior ciliary short artery alongside paracentral acute middle maculopathy (PAMM). A 48-year-old male patient presented with a sudden loss of vision in the upper left visual field and a slight decrease in visual acuity. Multimodal imaging, including scanning laser ophthalmoscope (SLO) imaging, revealed a “tongue-shaped” region of normal retina with mild retinal edema both above and below the optic disk. Fluorescein angiography (FA) exhibited minor delays in arterial perfusion and venous reflux, and a “tongue-shaped” area of normal retina was observed, with delayed hypofluorescence in the retinal areas above and below the optic disk, coupled with diminished choroidal background fluorescence, forming a “triangle” that pointed toward the optic disk. Optical coherence tomography (OCT) revealed retinal edema and hyperreflective bands within the inner nuclear layer and mild thickening of the inner retina. PAMM arises from inner retinal vascular lesions leading to macular hypoperfusion; however, its occurrence in the context of choroidal ischemic diseases is seldom documented. Consequently, this case provides novel perspectives on the retinal blood supply system.